Single-phase hybrid active power filter with adaptive notch filter for harmonic current estimation - Mekhilef, Saad; Tarek, M.; Abd Rahim, N. (2011)
This paper presents a digital implementation of a new and simple control technique for single-phase Hybrid Active Power Filter (HAPF). The main control consists of an accurate estimation technique used to extract harmonic current generated by nonlinear loads. The estimation of harmonic current is done by using multiple units of an Adaptive Notch Filter (ANF) linked together in parallel structure; each unit is used to estimate a specified harmonic component. The frequency estimation is then carried out based on the output of these units. Therefore, the sum of these harmonic components will be the reference signal for the active power filter to generate the appropriate compensation signal. A laboratory prototype model of the HAPF was developed and its control strategy was implemented digitally in TMS320F2808. The theoretical expectations were verified and demonstrated experimentally.